The Iron Intake Dismenore in Adolescent Girls - Putri, Dian Purnama (International Journal of Clinical Inventions and Medical Sciences (IJCIMS), 2023)
The problem of dysmenorrhea in adolescent girls is still one of the main health problems. The prevalence of dysmenorrhea in Indonesia is 64.25%, consisting of 54.89% primary dysmenorrhea and 9.36% secondary dysmenorrhea. One of the causes of dysmenorrhea is a lack of iron intake, iron plays a role in the formation of hemoglobin. Lack of iron intake can disrupt the formation of hemoglobin, so that the amount of hemoglobin in red blood cells will also decrease. The condition of low hemoglobin in red blood cells, causing the body to lack oxygen will cause anemia and dysmenorrhea. The aim of this study was to determine the relationship between iron intake and the incidence of dysmenorrhea in young women at MA Darul Ulum Palangka Raya. This type of research is observational analytic with cross sectional design. The sampling technique used is a non-probability sampling technique with a purposive sampling approach. The sample of this research was young women of MA Darul Ulum Palangkaraya, totaling 55 respondents. The results of the Chi-Square Test analysis are a p value of 0.000 (α<0.05) which proves that there is a relationship between the independent variable (iron intake) and the dependent variable (dysmenorrhea incidence). There is a relationship between iron intake and the incidence of dysmenorrhea in young women at MA Darul Ulum Palangkaraya.